ANALISIS SISTEM AKUNTANSI KEUANGAN DAERAH PADA BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA PROVINSI KALIMANTAN TIMUR - Heriyanto, Mita Prastiya, Titin Ruliana (EKONOMIA, 2017)
Regional financial accounting system is a set of procedures ranging from data collection, recording, summarizing, financial position report and Regional Government financial operations.The purpose of this study is to know and analyze the suitability of the regional financial accounting system implementation in terms of recognition, measurement  also expenditures and burden records at BPMPD Prov. Kaltim in 2016. The problems outline formulated as follows, how the recognition, measurement and expenditures and burden records done at BPMPD Prov. Kaltim based on Local Regulation Number 13 of 2008 about Principles of Regional Finance Management.Basic Theory in this study is public sector accounting that focuses on recognition, measurement  also expenditures and burden records. The hypothesis in this study is the recognition of expenditures and burden records at BPMPD of East Kalimantan province is not in accordance with  East Kalimantan Local Regulation Number 13 of 2008, the measurement expenditures and burden records at BPMPD of East Kalimantan province is not in accordance with  East Kalimantan Local Regulation Number 13 of 2008 and the records of expenditures and burden at BPMPD of East Kalimantan province is not in accordance with  East Kalimantan Local Regulation Number 13 of 2008.The analytical tool used in this study is a comparison analysis that compares the recognition, measurement and expenditures and burden records at BPMPD Prov. Kaltim with Local Regulation Number 13 of 2008.The Results of analysis and discussion show that BPMPD Prov. Kaltim has carried out the recognition, measurement and recording of expenditures and burden based on guidance of Local Regulation Number 13 of 2008, but in burden journal record and expenditure, BPMPD Prov. Kaltim has not implemented in accordance with Local Regulation Number 13 of 2008, due to the absence of journalization using the down payment account, the return of the remaining money and burden, using only the expenditure account. Based on the analysis result, the recognition of expenditure and burden at BPMPD Prov. Kaltim is in accordance with Local Regulation Number 13 of 2008, then the hypothesis is rejected. The measurement of expenditure and burden at BPMPD Prov. Kaltim is in accordance with Local Regulation Number 13 of 2008, then the hypothesis is rejected. Recording The expenditures and burden records at BPMPD Prov. Kaltim is not in accordance with Local Regulation Number 13 of 2008, then the hypothesis is accepted.